Free Electron Laser Measurement of Liquid Carbon Reflectivity in the Extreme Ultraviolet - Sumana L. Raj; Shane W. Devlin; Riccardo Mincigrucci; Craig P. Schwartz; Emiliano Principi; Filippo Bencivenga; Laura Foglia; Alessandro Gessini; Alberto Simoncig; Gabor Kurdi; Claudio Masciovecchio; Richard J. Saykally (Photonics, 2020)
Ultrafast time-resolved extreme ultraviolet (EUV) reflectivity measurements of optically pumped amorphous carbon (a-C) have been performed with the FERMI free electron laser (FEL). This work extends the energy range used in previous reflectivity studies and adds polarization dependence. The EUV probe is known to be sensitive to lattice dynamics, since in this range the reflectivity is essentially unaffected by the photo-excited surface plasma. The exploitation of both s- and p-polarized EUV radiation permits variation of the penetration depth of the probe; a significant increase in the characteristic time is observed upon increasing the probing depth (1 vs. 5 ps) due to hydrodynamic expansion and consequent destruction of the excited region, implying that there is only a short window during which the probed region is in the isochoric regime. A weak wavelength dependence of the reflectivity is found, consistent with previous measurements and implying a maximum electronic temperature of 0.8 eV ± 0.4.